Investigating the quality and drivers of sustainability reporting in the electricity industry : a global context : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accounting at Massey University, Albany, New Zealand - Marasigan, Alva (Massey University, 2024)
This research investigates the quality and determinants of sustainability reporting in the electricity industry, in particular the electricity generation sector. Electricity is a major driver of economic development and a major influence on climate change, hence an interesting setting for this study. Understanding the trends and determinants relating to the quality of sustainability reporting (QSR) may contribute to improved QSR and consequential improvements in transparency, accountability, and value creation. Part 1 of this study is qualitative and investigates the QSR of 100 electricity generators included in the S&P Platts Top 250 Global Energy Companies Rankings for 2021. The assessment of QSR is based on the qualitative characteristics of reporting, namely relevance (including materiality) and reliability. Content analysis of sustainability disclosures during 2018-2020 suggests the QSR of sample companies is relatively high and improving over time. Companies in countries with mandatory sustainability reporting regimes generally tend to achieve higher QSR. Part 2 of this study is quantitative and concerns testing selected determinants of QSR through regression analyses. Findings suggest that sustainability performance, use of the Global Reporting Initiative framework, and institutional shareholding have significant positive impacts on all QSR measures, while foreign shareholding has the same effect on relevance and overall QSR (contemporaneous as well as one-year lagged effects). Rule of law and carbon pricing policy have significant negative effects on relevance (contemporaneous as well as one-year lagged effects) while gender diversity shows the same effect on reliability (one-year lagged effect only). Rule of law also has a significant negative influence on overall QSR but only when testing for one-year lagged effects. Robustness and additional tests support these results. This study extends the existing literature on sustainability reporting by providing a holistic longitudinal, global, as well as an environmental, social, and economic perspective on QSR in the electricity industry. It also covers a wider range of QSR determinants than most others and improves on the precision of QSR measurement. This study may be useful to regulators and standard setters in their efforts to harmonise sustainability reporting and provides useful insights to decision makers and practitioners on the need to link sustainability disclosures to sustainability performance, as well as stakeholder activities, assurance considerations, and materiality.
Keywords: quality of sustainability reporting (QSR), relevance including materiality, reliability, overall QSR, determinants, sustainability reporting; Electric power production; Accounting; Social responsibility of business; Auditing; Sustainable development reporting; Evaluation; 350107 Sustainability accounting and reporting